Semiconductor nanomaterials for flexible technologies : from photovoltaics and electronics to sensors and energy storage/harvesting devices - Sun, Yugang; Rogers, John A., 1967- (William Andrew, 2010)
This book is an overview of the strategies to generate high-quality films of one-dimensional semiconductor nanostructures on flexible substrates (e.g., plastics) and the use of them as building blocks to fabricating flexible devices (including electronics, optoelectronics, sensors, power systems). In addition to engineering aspects, the physics and chemistry behind the fabrication and device operation will also be discussed as well. Internationally recognized scientists from academia, national laboratories, and industries, who are the leading researchers in the emerging areas, are contributing exceptional chapters according to their cutting-edge research results and expertise. This book will be an on-time addition to the literature in nanoscience and engineering. It will be suitable for graduate students and researchers as a useful reference to stimulate their research interest as well as facilitate their research in nanoscience and engineering. Considers the physics and chemistry behind fabrication and device operation Discusses applications to electronics, optoelectronics, sensors and power systems Examines existing technologies and investigates emerging trends.
Keywords: Semiconductor films.; Nanostructured materials.; Nanostructures.; elektronické knihy; electronic books